Sustainable environments: ecological, economic, sociocultural and statistical aspects invited papers - Ghosh A K ed.; International Workshop on Statistical Science and Environmental Policy: Possible Interactions; International workshop on statistical science and environmental policy: possible interactions Kolkata, India 10-12 Jan 2000 (Kolkata ISI, 2004)
This volume comprises eight selected contributions on the important environmental issues by renowned subject experts. The papers deal with environmental data base, basic concepts, ecological and social issues and their interrelationships, mostly in the indian context. The major environmental theme areas discussed in the Workshop were: Environmental databases, Environmental modeling, Environment and Sustainability, Global Environmental change, Pollution and Environment and Society. The thrust was on statistical models, methods and innovative computational and inferential tools for design, collection, analysis, and monitoring of environmental data.
Keywords: Environmental science; Sustainable development